KOMPAK: Translation, cross-cultural adaptation, and validation of an instrument for assessing interprofessional collaboration between pharmacists and physicians in Indonesia - Amin, Irnawati H.; Massi, Muhammad N.; Wahyudin, Elly; Bahar, Muhammad A.; Hadju, Veni; Niamuzisilawati, Eva; Munawwaroh, Makiyatul; Utami, Ikrimah N.; Ardiansyah, Akhmad; Alkaff, Sylmina D.; Arifin, Bustanul (Narra Sains Indonesia, 2025)
Interprofessional collaboration is crucial for addressing the complexity of health problems, requiring contributions from various professions to enhance healthcare quality, improve patient satisfaction, and achieve better clinical outcomes. The aim of this study was to develop and validate the physicians and pharmacists collaborative practice instrument, known as KOMPAK (Kolaborasi Medis Persepsi Apoteker dan Dokter/Medical Collaboration: Perceptions of Pharmacists and Physicians) for use in Indonesia. A cross-sectional study was conducted across the western, central, and eastern rigors of Indonesia, targeting physicians and pharmacists. The study included translation (forward and backward), cross-cultural adaptation (with 30 participants), and validation using confirmatory factor analysis (CFA) among 315 physicians and 315 pharmacists. The present study found no significant changes emerged during the translation and adaptation phases. In the validation phase, the CFA results for the physician instrument indicated a Comparative Fit Index (CFI) of 0.94 (>0.92), Tucker-Lewis Index (TLI) of 0.93 (>0.92), Root Mean Squared Error of Approximation (RMSEA) of 0.055 (<0.07), Standardized Root Mean Residual (SRMR) of 0.07 (<0.08), and Cronbach’s Alpha reliability of 0.88. The pharmacist instrument yielded similar results with a CFI of 0.94 (>0.92), TLI of 0.93 (>0.92), RMSEA of 0.06 (<0.07), SRMR of 0.05 (<0.08), and Cronbach’s Alpha reliability of 0.83. The final instrument consists of 24 items. In conclusion, the KOMPAK instrument demonstrated validity and reliability, supporting its use for measuring interprofessional collaboration between physicians and pharmacists in Indonesia.